2015
DOI: 10.5830/cvja-2015-038
|View full text |Cite
|
Sign up to set email alerts
|

The burden of stroke in Africa: a glance at the present and a glimpse into the future: review article

Abstract: SummaryObjectiveInformation on the current burden of stroke in Africa is limited. The aim of this review was to comprehensively examine the current and projected burden of stroke in Africa.MethodsWe systematically reviewed the available literature (PubMed and AJOL) from January 1960 and June 2014 on stroke in Africa. Percentage change in age-adjusted stroke incidence, mortality and disability-adjusted life years (DALYs) for African countries between 1990 and 2010 were calculated from the Global Burden of Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
299
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(331 citation statements)
references
References 81 publications
(163 reference statements)
7
299
2
1
Order By: Relevance
“…The consequences are increased loss in productivity, reduced labour efficiency and increased comorbidity with poorer outcomes [2] and [35]. Evidence of these have been shown among survivors who were on self-medication using locally sourced treatment due to inaccessibility of low-cost neurological care and prohibitive out-of-pocket cost for conventional drugs with proven efficacy [5]. The finding of this study has huge socioeconomic and wider health implication in a rural community in Niger Delta and may help policymakers particularly in LMICs institute effective public health response.…”
Section: Implication Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequences are increased loss in productivity, reduced labour efficiency and increased comorbidity with poorer outcomes [2] and [35]. Evidence of these have been shown among survivors who were on self-medication using locally sourced treatment due to inaccessibility of low-cost neurological care and prohibitive out-of-pocket cost for conventional drugs with proven efficacy [5]. The finding of this study has huge socioeconomic and wider health implication in a rural community in Niger Delta and may help policymakers particularly in LMICs institute effective public health response.…”
Section: Implication Of the Resultsmentioning
confidence: 99%
“…Due to the current epidemiological transition driven by rapid economic development and combined effects of population growth and aging, and sociocultural changes, there is huge concern of continuous increase in the prevalence of stroke in LMICs including Nigeria, and among relatively younger populations [2]. Recent systematic review of population-based studies revealed a consistent evidence that the prevalence of stroke and its major risk factors particularly high blood pressure were now higher in LMICs compared to high income countries and that young adults who present with stroke were unaware of their high blood pressure [2], [5], [6] and [7]. These important revelations were poorly known or underexplored in the rural areas of most LMICs such as in the Niger Delta region in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…wide pooled estimate without due consideration of human development index and gross national income per capita estimates [6,51]. Our study presents the most comprehensive and up-to-date review of stroke prevalence in LMICs.…”
mentioning
confidence: 99%
“…Perhaps the greatest impact of mHealth for poststroke care could be harnessed in low and middle income countries (LMIC) were stroke prevalence is escalating at alarming rates (15)(16)(17), and profound disparities exist in access to specialized care due to paucity of neurologists and specialist physicians. In these LMIC settings, taskshifting strategies with greater participation by nurses as liaisons between stroke patients and physicians via mHealth technology could be worth exploring, if all the stakeholders were interested and engaged.…”
mentioning
confidence: 99%